Humans who chance the world - Ponyatyh, M.; Sychev, V. (ТДАТУ, 2018)
EN: The article presents a brief biogmphy of a person who should stand alongside such distinguished people as Stephen Hocking, Albert Einstein and other brilliant scientists. UK: У статті представлена коротка біографія людини, яка повинна бути нарівні з такими видатними особистостями як Стівен Хокінг, Альберт Ейнштейн та іншими блискучими вченими.
Keywords: Elon Musk; perseverance and commitment to success; PayPal; start-up; стартап